Musical Ritual and Ritual Music - Brita Renée Heimarck (Muzikološki Zbornik, 2022)
This article explores music as a religious ritual accompaniment within the realm of Balinese Hinduism in Bali, Indonesia, and the spiritual dimensions of music as a “tool” and a “ritual” in itself, within the Hindu-based Siddha Yoga practices and philosophies of sacred sound and the devotional worship of arati.